2021
DOI: 10.1155/2021/6676301
|View full text |Cite
|
Sign up to set email alerts
|

Complete Penoscrotal Transposition with Other Extragenital Anomalies in a Neonate Delivered at Term

Abstract: A complete penoscrotal transposition (CPST) is a very uncommon congenital maldevelopment that is always associated with other abnormal body variations (malformations). We report a rare case of a term neonate delivered with CPST, which had a flaccid penis and an intact scrotum with unilateral limb and digital deformity, imperforate anus, cardiac malformation a facial deformity. Neonate died two hours after delivery. The foetal abnormality was not detected through routine antenatal services received by the mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Complete major PST is a rare heterogeneous condition that result from abnormal genital tubercle development around the 6th week of gestation. 7,23 In this study, the lower incidence of complete major PST reflects the small number of hypospadias patients who might have abnormal penile development starting at nonhormonal phase when the development of genital tubercle occurred. Severe form of BS was also found in the majority of severe hypospadias cases in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Complete major PST is a rare heterogeneous condition that result from abnormal genital tubercle development around the 6th week of gestation. 7,23 In this study, the lower incidence of complete major PST reflects the small number of hypospadias patients who might have abnormal penile development starting at nonhormonal phase when the development of genital tubercle occurred. Severe form of BS was also found in the majority of severe hypospadias cases in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Although rare, scrotal anomalies are often found together with hypospadias. 5,[7][8][9] Currently, studies discussing scrotal anomalies in hypospadias are limited and mostly reported through case reports. A study by Fahmi et al discusses scrotal position disorders in children comprehensively but not specifically for children with hypospadias.…”
Section: Introductionmentioning
confidence: 99%
“…PST has been shown to frequently present with associated genitourinary defects, including hypospadias, chordee, and cryptorchidism (Arena et al, 2005; Fahmy et al, 2014; Parida et al, 1996; Pinke et al, 2001; Sexton et al, 2015). PST also co‐occurs with other congenital defects outside of the genitourinary system (e.g., gastrointestinal and cardiac abnormalities) (Ayamba et al, 2021; Parida et al, 1996; Pinke et al, 2001) though the largest study to date describing birth defects co‐occurring with PST included only 53 patients (Pinke et al, 2001). An analysis of these co‐occurring defects in a large population‐based sample is warranted.…”
Section: Introductionmentioning
confidence: 99%